KELEMAHAN ELECTRONIC TRAFFIC LAW ENFORCEMENT DALAM MENINDAK PENGGUNAAN TANDA NOMOR KENDARAAN BERMOTOR PALSU - Marten Ferryanto; Nurhayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Traffic has a vital role towards the mobility of the people, as well as the distribution of goods, so it is regulated in Law number 22 of the year 2009. One of the serious violations that often happened is the usage of fake vehicle registration plate (TNKB), that will disrupt the vehicle identification system. Polri responded by implementing the Electronic Traffic Law Enforcement (ETLE) system as the innovation of digital law enforcement. However, the ETLE system still have weaknesses in identifying fake vehicle registration plate. This research will review the effectivity of ETLE in MT.Haryono road of South Jakarta, as well as analyzing the factors that causes the weak enforcement against such violations in order to contribute to the improvement of the traffic law enforcement system in Indonesia. The research method that will be used in this research is the Empirical Legal method by gathering the primary data from interviews towards the ETLE operators. The secondary data will be gathered from scientific articles as well as previous research journals that examine about law rules that is relating to ETLE. The research result will explain about the working mechanism of the ETLE system on how it enforces the law towards traffic violator from the process of recording the violation until the payment of the fine. The online traffic fine ticketing, on its base is just the same as manual ticketing, it's just that online ticketing is implemented so that the law enforcer can work transparently and can have accountability in the process of law enforcing, However there is a weakness of the online ticketing in the law enforcing process. One of them is that ETLE could not detect the usage of fake vehicle registration plate that is caused by network issue as well as unsynchronized data and the technology limitation to detect fake vehicle registration plate (TNKB) because there is no regulation towards the material nor the font of its making.